The Factors Influencing the Incidence, Persistence, and Severity of Symptoms After SARS-CoV-2 Infection in Chinese Adults: A Case–Control Study - Weixiao Wang; Runjie Qi; Siyue Jia; Zhihang Peng; Hongxing Pan; Ming Xu; Yuanbao Liu; Xiaoqiang Liu; Qing Wang; Li Zhang; Jihai Tang; Hao Yang; et al. (Tropical Medicine and Infectious Disease)
Following the emergence of COVID-19, breakthrough SARS-CoV-2 infections have demonstrated substantial heterogeneity in both occurrence and clinical severity. This case–control study aimed to elucidate the factors associated with the incidence, duration, and severity of SARS-CoV-2 symptoms among Chinese adults during the Omicron wave. The analysis was based on data from a national COVID-19 surveillance program encompassing six provinces—Jiangsu, Chongqing, Shandong, Hunan, Anhui, and Yunnan—and included both laboratory-confirmed and clinically diagnosed cases. Data were systematically collected between February and April 2023. For each confirmed case, a matched control was selected through simple random sampling, matched on sex, age (±5 years), and province of residence. Multivariate logistic regression analyses were employed to assess a range of potential determinants, including demographic characteristics, lifestyle behaviors, and pre-existing medical conditions, in relation to the risk of infection, as well as the persistence and severity of symptoms following SARS-CoV-2 breakthrough infection. A total of 10,426 cases and 10,426 matched controls were included in the final analysis. Among the infected individuals, 963 (9.24%) reported persistent symptoms, while 773 (7.41%) experienced moderate-to-severe clinical manifestations. Occasional alcohol consumption, presence of comorbidities, tea and coffee intake, overweight status, and a longer interval since the last vaccination dose were all significantly associated with increased odds of infection (OR > 1, FDR < 0.05). Conversely, weekly alcohol consumption and smoking were associated with a decreased risk (OR < 1, FDR < 0.05). Female sex was significantly associated with both persistent and moderate-to-severe symptoms. Additional risk factors for prolonged or severe symptoms included older age, being underweight or overweight, a history of immunotherapy, coffee consumption, and the presence of comorbidities. These findings underscore the multifactorial nature of SARS-CoV-2 infection outcomes and highlight the interplay between host characteristics and behavioral factors. The results support the development of personalized prevention strategies aimed at reducing the clinical burden and long-term impact of COVID-19.